URGENSI PSIKOLOGI DAN AKTUALISASINYA DALAM PENDIDIKAN DASAR ISLAM - Siti Aqlima; Wardiana; Nurbayani (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2022)
The urgency of Islamic education psychology is very important in the orientation of Islamic education in Indonesia. Islamic education psychology is very concerned about the principles and foundations of Islamic education in Indonesia. The purpose of this study is to try to pave the way for Islamic education in Indonesia related to the urgency of psychology and its actualization in Islamic education. This study is very relevant to use literature studies by relying on bibliographies of variants of scientific publications such as books, international scientific articles and other literature. The results of this study indicate that the urgency of psychology in Islamic education as a reference in general is psychology with an insight into the Qur'an and al-Hadith. Which in the end produces God-oriented output, humans are happy in this world and the hereafter. While psychology includes developmental psychology, learning psychology and social psychology. Psychology in the perspective of Islamic education also strives for teachers as educators to plan and implement education in accordance with the stages of psychological development of children so that children's abilities and potentials can develop to the fullest. The urgency of psychology in Islamic education must specifically look at the psychological condition of the individual. In this case students in particular must achieve learning and totality in implementing the existing curriculum.